Determining a Global Mid-Upper Arm Circumference Cutoff to Assess Underweight in Adults (Men and Nonpregnant Women) - Tang, Alice M.; Chung, Mei; Dong, Kimberly; Wanke, Christine; Bahwere, Paluku; Bose, Kaushik; Chakraborty, Raja; Charlton, Karen; Hong, Steven; Nguyen, Phuong Hong; Patsche, Cecilie B.; Deitchler, Megan; et al. (FHI 360, 2017)
Numerous studies have shown that mid-upper arm circumference (MUAC) correlates well with body mass index (BMI) in adult populations. However, globally applicable MUAC cutoffs have not been established to classify undernutrition among adults. Increasingly, MUAC is being used to assess nutritional status and to determine eligibility for services among adults, especially in people living with HIV and/or tuberculosis. Many countries and programs have established their own MUAC cutoffs to determine eligibility for program services, but there is limited evidence supporting these cutoffs and it is not known whether the cutoffs are optimal.